High pressure mist for fire suppression - VUOLLE, Pasi (Tunnels & Tunnelling International, 2010)
The A86 West tunnel in Paris, protected by high-pressure water mist system, is probably the world's largest tunnel protected by an active fire protection system. This tunnel is a feat of engineering and design at 1 0 km long with two superimposed levels, one in each direction. Each level has two traffic lanes and a hard shoulder. Reserved for light vehicles, the tunnel is equipped with all the latest safety devices, exceeding the requirements of new French regulations governing tunnel safety. In the project planning phase, seven tunnel segments were identified as requiring an active fire protection system. A number of different water mist systems were subject to full-scale fire testing. The results convinced the road authority that it was possible to design and build a water mist system to handle the M30's extra-wide tunnel sections and potentially large fire loads (HGVs) while using modest amounts of water compared to traditional deluge systems. The seven tunnel segments designated as requiring active fire protection are now protected by water mist systems. The Helsinki service tunnel was built in 2007-2009 and is protected by Finland's first automatic tunnel fire protection system. The total length of this tunnel is 2 km and it connects several commercial centres of the city and e.g. the University of Helsinki including their parking facilities and service tunnels. Service tunnel will allow city to expand its pedestrian zones by guiding especially the service traffic into the tunnel. The climate in Finland can be extreme cold during the winter and therefore a thermal protection is needed for the water mist system piping: a trace heating system was installed for the main tubes affected by low temperatures. Roads in Finland are treated with salt to prevent icing in temperatures just below zero. All the pipes and components are made of high-grade stainless steel grades in order to give the best protection against corrosion in aggressive tunnel environments. This will naturally prolong the life-time of the water mist system. Marioff's high pressure water mist technology combined with professional service presented the most economical solution for the Helsinki service tunnel.